Prospects for Blue-Green Infrastructure in Maribor - Vovk, Ana (Journal for Geography, 2023)
Cities are facing the consequences of climate change, including higher summer temperatures and increased frequency of intense precipitation, leading to flooding issues due to impermeable surfaces. The lack of green spaces causes extreme temperatures and a decrease in biodiversity, which is modest in urban areas. Consequently, recent years have seen the introduction of approaches based on mimicking natural processes, referred to as blue-green infrastructure. These are designed areas that enable water retention and purification, contribute to increased biodiversity, and positively impact quality of life. This article presents the possibilities for implementing blue-green infrastructure in Maribor, based previously executed projects.